The Economic Efficiency of Traditional and Islamic Banking (a Comparative Analysis of the Turkish, Azerbaijani, and Iranian Banking Sectors) - Mayis G. Gulaliyev; Elmar N. Rahimov; Flora Sh. Kashiyeva; Alida T. Huseynova; Shahla M. Alijanova; Yegana A. Hakimova (Comparative Economic Research. Central and Eastern Europe, 2021)
The article attempts to develop a methodology for a comparative assessment of the economic efficiency of banks, including traditional and Islamic banking mod- els. The assessment shows that the stability of financial institutions in Azerbaijan is lower compared to banks where Islamic banking is used. The assessment also shows that there is a strong dependence of the GDP growth rate on the sub-in- dices of the effectiveness of financial institutions in Azerbaijan, Turkey, and Iran. The methodology of linear regression and a composite index of the economic ef- ficiency of banks are applied. The assessment shows that the influence of the sta- bility of the financial system on economic growth in Azerbaijan, Iran, and Turkey is different. The economic growth rate and the ratio of bank loans to bank deposits in Azerbaijan and Turkey are positively related, but negatively in Iran.
Keywords: G21; 330; financial institutions; access to financial institutions; the depth of financial institutions; the effectiveness of financial institutions; the stability of financial institutions